2010
DOI: 10.1128/jvi.01687-09
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Immunogenicity of Subtype A Human Immunodeficiency Virus Type 1 Envelope Exhibiting Differential Exposure of Conserved Neutralization Epitopes

Abstract: Development of broadly cross-reactive neutralizing antibodies (NAbs) remains a major goal of HIV-1 vaccine development, but most candidate envelope immunogens have had limited ability to cross-neutralize heterologous strains. To evaluate the immunogenicity of subtype A variants of HIV-1, rabbits were immunized with pairs of closely related subtype A envelopes from the same individual. In each immunogen pair, one variant was readily neutralized by a variety of monoclonal antibodies and plasma antibodies, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
19
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 70 publications
(75 reference statements)
4
19
0
Order By: Relevance
“…Only tier 1A viruses were neutralized at moderate to high levels, and similar to previous vaccine studies (12,17,19,35,36,48), almost no autologous neutralization was elicited (data not shown). This lack of autologous neutralization and limited heterologous neutralization compared to the moderate cross-clade neutralization breadth in the infected VC10014 and VC20013 subjects could be explained by several factors.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Only tier 1A viruses were neutralized at moderate to high levels, and similar to previous vaccine studies (12,17,19,35,36,48), almost no autologous neutralization was elicited (data not shown). This lack of autologous neutralization and limited heterologous neutralization compared to the moderate cross-clade neutralization breadth in the infected VC10014 and VC20013 subjects could be explained by several factors.…”
Section: Discussionsupporting
confidence: 62%
“…Prolonged antigenic exposure is a key clinical parameter associated with the natural development of bNAbs in elite neutralizers (24,(31)(32)(33), suggesting that the dynamic interactions occurring between viral quasispecies and host B cells result in continuously changing antibody specificities in vivo (24,25) and likely contribute to the generation of bNAbs (34). In fact, multiple pathways to neutralization breadth have been shown in different subjects (9,33,(35)(36)(37)(38), whereas in some subjects, antibodies with a single specificity or a few specificities can account for much of the neutralization activity (10,29,33,(39)(40)(41)(42). Thus, further understanding of the humoral response in infected individuals who naturally develop bNAbs could guide the selection of candidate Env immunogens and the design of vaccine strategies that elicit breadth (43).…”
mentioning
confidence: 99%
“…Such broad anti-HIV neutralizingantibody responses have not yet been achieved by immunization (1,3,8,11,13,17,21,25,26,35,40,42,58,63,66). Initially, it was thought that such antiviral responses are extremely rare, even in the context of natural HIV-1 infection, and therefore, their elicitation by vaccination would be extremely difficult, if not impossible.…”
mentioning
confidence: 99%
“…Thus, efforts to design vaccines that rapidly elicit an effective and broadly cross-reactive neutralizing Ab (nAb) response seem rational based primarily on the observation that doses of bNmAbs are the only formula to date that has been shown to prevent infection and to provide sterilizing immunity in NHP. Despite multiple efforts to develop an immunogen or immunogens that can elicit bNAbs following vaccination, success has been limited (12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Some incremental advances have been made, including our recent immunogenicity studies (22) and those of others (23)(24)(25) that have shown an advantage of coimmunization with DNA and protein immunogens, including the potential of contracting the vaccine regimen to a small number of immunizations to reach peak NAb responses.…”
mentioning
confidence: 99%